Factors that contribute to prolonged hospital stay after discharge among surgical patients in a tertiary hospital in North Central Nigeria - Benjamin I Akhiwu; Helen AKHIWU; Josiah Miner Njem; Basil Ojukwu; Ukachi Chiwendu NNAWUIHE; Solomon Akoji ALU; Agida Samuel ADOGA; Akinola LADEINDE (Nigerian Dental Association, 2024)
Background: Surgical practice has hospitalization of patients for surgery and treatment as an inherent part of it; after which the patients are found fit for discharge. There is however a group of patients who remain on bed even after they have been deemed fit for discharge. This study aimed to determine the number of days surgical patients classified as having prolonged stay remain in hospital after they were deemed fit for discharge and identify the reasons for this. Methods: Surgical patients still on bed more than 48 hours after they were discharged who consented to participate in the study were recruited. Results: A total of 341 patients were recruited. The mean duration of stay after discharge was 17.6± 13 days. The specialty with the highest number of patients was Neurosurgery. Lack of finance and absence of a caregiver were the causes (96.5% and 3.5% respectively). The top three suggestions by patients on how to reduce prolonged hospital stay were bill waiver for indigent patients, reduced cost of health care services and financial aid by philanthropists. Conclusion: The mean number of days patient remained in hospital after discharge was 17.6 days. Financial reasons and absence of a caregiver are the major reasons for prolonged hospital stay. There is a need for a multi-sectoral approach to improve enrollment in the National Health Insurance Scheme and provide social support for patients in need of care post-discharge to reduce the adverse effects of prolonged hospital stay on the hospital and patients.